A Survey of Prosthodontics Techniques Applied by Dental Practitioners in Sulaimani City - Al-Kaisy, Neda (Journal of Baghdad College of Dentistry, 2016)
Background: Prosthodontic services have changed markedly due to an introduction of new materials, techniques and treatment options. The aim of this study were to identify the type of materials and the methods used by dental practitioners in their clinics to construct conventional complete dentures and to specify the type and design for removable partial dentures (RPDs); and to then compare them with those taught in dental schools. Materials and methods: A total of 153 dental practitioners in Sulaimani city completed a written questionnaire. The questionnaire included 19 questions regarding complete and RPDs fabrication. Results: Most of the practitioners provide complete dentures (81.6%) and RPDs (95.3%) in their clinics. Polyvinyl siloxane 38.4% and irreversible hydrocolloid 37.6% impression materials were most commonly used to make the preliminary and zinc oxide eugenol 52% for final impressions. The majority of participants did not disinfect their impressions (73.9%). In order to establish the vertical and centric relations, different methods were used. Many practitioners depend on dental technicians to determine the post-dum area (42.4%) and all of them faced different problems during fabrication of the complete denture. Acrylic RPDs were the main type of RPDs provided (89.7%), followed by flexible partial dentures (70.5%). The minority constructed cast metal RPDs (18.4%).Conclusions: Private practitioners did not perform most of the techniques nor use the procedures or materials that are being taught in dental schools. There is a need for continuing dental education programs for improving their clinical skills. Moreover reassessing of the prosthodontic curriculum of the related dental schools is required.